EUROPEAN TRANSPORT POLICY AND ACCIDENT FREQUENCY IN SR IN 2006 - Grendel, Peter (Doprava a spoje, 2007)
Given article deals with the issues of synchronization of the European transport policy and situations on Slovak Republic roads. EU's basic objective in this sphere is reduction of fatality rate on roads until 2010 in 50% as compared with 2002. The article shows statistical data on accidents frequency in the SR and on reasons for their occurrence. Conclusion of the article is devoted to some measures prepared by the SR Government Board of road transport safety in relation to reduction of road accidents frequency.